PENERAPAN PENDIDIKAN AGAMA ISLAM DALAM LINGKUNGANKELUARGA (Studi Kasus di Desa Ellak Daya Kecamatan Lenteng Kabupaten Sumenep) - Hasib; Abdul Rouf; Dian Triana (FAI- Undar, 2020)
Education in the family is fundamental education or the basis of the next child's education. Religious education is the first and foremost education that is needed for children. Where it directly affects the behavior and development of children. While religious education in Muslim family children is the beginning of personality formation, good or bad the child's personality depends on the education and environment that nurtures him. Therefore, as a Muslim family, parents have an obligation to provide education and guidance to their children. Given the importance of religious education, parents must have sufficient knowledge in upholding the pillars of religious education in the family.This study aims to determine the application of Islamic religious education in the family environment. In the discussion of the thesis used theoretical and empirical approaches. Theoretically sourced from the literature and empirically carried out by searching, observing, and processing data from the field, which took objects in Ellak Daya Village, Lenteng District, Sumenep Regency. This research uses interview, observation, and documentation methods. To obtain data regarding the application of Islamic religious education in the family environment, data reduction, data presentation, conclusion and verification were used. To achieve this goal, the data were analyzed by qualitative descriptive analysis.The results of the study briefly show that the implementation of religious education for the children of Muslim families in Ellak Daya can be said to be good. This can be proven by the attitude of parents who always pay attention to and instruct their children to pray, provide aqidah, worship and moral education materials using habituation methods and other methods, and provide good examples or examples to their children.